Map Collections and the Internet: Some Ideas about Various Online Map Services, Based on the ETH Map Collection in Zürich - Jürg Bühler (Liber Quarterly: The Journal of European Research Libraries, 2000)
The Internet enables a map collection to be easily available to the general public. The Internet allows worldwide usage of map libraries. It is well suited for public relations and therefore important for today’s map libraries.